Penerapan Algoritma Transformasi Walsh-Hadamard dalam Pemampatan File BMP - Ainun Mardiah; Berto Nadeak (Journal of Computer System and Informatics (JoSYC), 2022)
The size of the image file in the bmp format is relatively large, where the better the quality of the resulting image, the larger the pixel size required to record the image, the compression process is one of the alternatives that is needed to reduce the capacity of an image file, so that it is not too wasteful in using space storage. With the size of a data that has been reduced or bit reduced to an image file, when moving or sending an image file that has been bit done, the process of moving the file will be easier and faster. because the storage space media has enough space to store an image file that has scattered bits or the compression process of a file that has been moved. The compression technique in the application uses the Walsh Hadamard Transformation algorithm to produce a compressed image and change the initial size, image character content, and parameters for compression of Cr (Compression Ratio) in reducing file size.